BROADCASTING, POWER ON MINORITY, AND PUBLIC OPINION: MEDIA DISCOURSE AND STATE CONTROL IN INDONESIA'S NEW ORDER REGIME - Harmonis Harmonis; Firdaus Firdaus; Lilik Sumarni (Universitas PGRI Sumatera Barat, 2026)
This study investigates the complex relationship between state power, broadcasting institutions, and public opinion in Indonesia during the New Order regime under President Soeharto (1966–1998), with particular attention to how media discourse was structured to support political authority and marginalize minority voices. In an authoritarian media environment, broadcasting did not operate as a neutral public communication platform, but as a regulated instrument through which the state managed information, controlled access, and shaped ideological interpretation. Using a qualitative research design, this study draws on archival documents and interviews with media practitioners and broadcasting experts to examine how state policies influenced broadcasting ownership, licensing, editorial direction, and content production. The findings show that institutions such as TVRI and Radio Republik Indonesia functioned as strategic tools of state communication. At the same time, private broadcasters that emerged in the late New Order period remained tied to political and economic elites, limiting genuine media independence. The study further reveals that censorship, centralized supervision by the Ministry of Information, and selective tolerance of limited pluralism enabled the regime to project an image of openness while maintaining strict control over dissenting narratives. This condition not only reinforced regime legitimacy but also constrained public deliberation and weakened the visibility of minority perspectives in the national media sphere. By highlighting the intersection of media discourse, institutional control, and political authority, this study contributes to broader debates on authoritarian communication, media governance, and the political functions of broadcasting in Indonesia’s New Order era.